Alienation in Murakami’s Blind Willow, Sleeping Woman - Imam Imam (Universitas Pendidikan Indonesia (UPI), 2016)
This study explores alienation in Haruki Murakami’s Blind Willow, Sleeping Woman. It studies the aspects of alienation in three selected short stories from Blind Willow, Sleeping Woman: “A Folklore for My Generation: A Pre-History of Late-Stage Capitalism,” “Tony Takitani,” and “Firefly,” and how these aspects manifest in the lives of the people in the selected stories. To achieve the objectives, the study was conducted under postmodernist approach and employs Seeman’s theory on alienation known as Seeman’s Aspects of Alienation (1959) as the theoretical framework of the study. The findings divulge that there are four alienation aspects palpable in the selected short stories: powerlessness, meaninglessness, normlessness, and social isolation. They also disclose that the alienation aspects found manifest through four key points i.e. the unknown origins of alienation, the problem of choices overload, the fragmentation of life aspects, and disconnected relational self. Viewed from postmodern perspective, Murakami’s Blind Willow, Sleeping Woman can be interpreted as a representation of contemporary Japan as it portrays contemporary alienation issues, which are the effects of the breaking down of the Japanese traditional norms establishment, the grand narrative, in at least two occasions in Japanese history, Japan’s involvement and defeat in World War II and the student movement in the sixties.Keywords: Alienation, Postmodernism, Blind Willow Sleeping Woman